Religion, Race, and Discrimination: A Field Experiment of How American Churches Welcome Newcomers - Wright, Bradley R. Enter (Journal for the scientific study of religion, 2015)
This article reports the results of a nationwide audit study testing how Christian churches welcome potential newcomers to their churches as a function of newcomers' race and ethnicity. We sent email inquiries to 3,120 churches across the United States. The emails were ostensibly from someone moving to the area and looking for a new church to attend. That person's name was randomly varied to convey different racial and ethnic associations. In response to these inquiries, representatives from mainline Protestant churcheswho generally embrace liberal, egalitarian attitudes toward race relationsactually demonstrated the most discriminatory behavior. They responded most frequently to emails with white-sounding names, somewhat less frequently to black- or Hispanic-sounding names, and much less to Asian-sounding names. They also sent shorter, less welcoming responses to nonwhite names. In contrast, evangelical Protestant and Catholic churches showed little variation across treatment groups in their responses. These findings underscore the role of homophily, organizational homogeneity, and the costs of racial integration in perpetuating the racial segregation of American religious life.